ACTIVE PARTS AND SEED EFFICIENCY OF ERYNGIUM PLANUM FROM APIACEAE FAMILY - L. M. Eliseeva; E. A. Scherbakova; D. A. Konovalov; M. A. Galkin (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Eryngium planum L. is one of biperennial plants and hemicryptophyte. It is successfully introduced in cultivation in CMW conditions. The plant reaches 70 cm. One plant can contain up to 16 000 seeds. It is possible to obtain about 4.9 t/ha of air-dry weight, 4.2 t/ha of roots, and 3.59 hwt/ha of seeds from 1 ha.